From diagnosis to cure: The role os the Dentist in the treatment of oral cancer (Research, Society and Development, 2021)
Squamous cell carcionama (SCC) is a malignat neoplasm of epithelial origin that can affect the entire upper digestive and airways, from the oral cavity to the end of the oropharyngeal region. The dentist plays a major role in preventing oral cancer, especially when acting at the levels of primary and secondary prevention, by proposing actions that facilitate the recognition of individuals belonging to the risk group and by performing practices thet seek to diagnose injuries early suspicions. Objective: Report a case of squamous cell carcinoma, highligting the role of the dentist in the early diagnosis of the lesion and during cancer treatment. Case report: A 64-year-old female pactient, melanoderma, attended to the Dentistry Clinic of the Federal University of Ceará - Campus Sobral, with the main complaint of discomfort caused by prosthesis. The intraoral clinical examination revealed a nodular lesion with erythroleucoplastic color and fibrous consistency, located on the soft palate, measuring about 3 cm in diameter. Final considerations: The early diagnosis of oral cancer can provide an adequate therapeutic management and, consequently, a better prognosis.